2015
DOI: 10.12693/aphyspola.128.b-417
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Vibrational Studies of ±1-(1H-Benzoimidazol-2-YL) Ethanol, Using DFT Method

Abstract: In this study, conformational analysis and quantum chemical calculations of ±1-(1H-Benzoimidazol-2-YL) Ethanol were carried out. The geometric structure, infrared intensities, UV-VIS spectrum, HOMO-LUMO energies, 1 H and 13 C nuclear magnetic resonance (NMR) chemical shifts were calculated by using the density functional method (DFT/B3LYP) with 6-311++G(d,p) basis set. The vibrational studies were interpreted in terms of potential energy distribution (PED). Finally, calculated values were compared with the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The previous works of the 1,3-proton shift has shown that the barrier could drop significantly when the water molecule is involved, acting as a mediator [53][54][55][56][57][58][59][60][61][62][63][64][65]. Figure 5 shows the one-step nucleophilic addition mechanism for the monohydrated reaction between the methanol and CI.…”
Section: Potential Energy Surface For the Reaction Of Methanol With Cmentioning
confidence: 99%
“…The previous works of the 1,3-proton shift has shown that the barrier could drop significantly when the water molecule is involved, acting as a mediator [53][54][55][56][57][58][59][60][61][62][63][64][65]. Figure 5 shows the one-step nucleophilic addition mechanism for the monohydrated reaction between the methanol and CI.…”
Section: Potential Energy Surface For the Reaction Of Methanol With Cmentioning
confidence: 99%
“…The quantum mechanical calculations, performed using DFT enable one to investigate the structural, spectroscopic, electronic and nonlinear optical (NLO) properties of molecules [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The development of the computational techniques for applying DFT to real materials has made it possible to predict quantitatively the atomic and electronic structure and properties of different materials [6][7][8][9][10]. In particular, the pseudopotential method based on the local DFT [7][8][9][10][11] has been very successfully used for studying various properties of the crystals [8], surfaces, and interfaces of metals, ceramics, and semiconductors [12]. The first part deals with a concise description of the theoretical background; in the second part the structural and electronic aspects of both compounds were examined.…”
Section: Introductionmentioning
confidence: 99%